Results of high-risk neutropenia therapy of hematology-oncology patients in a university hospital in Uruguay - Burutaran,Matilde Boada (2015)
Background: Febrile neutropenia is an important cause of mortality and morbidity in hematology-oncology patients undergoing chemotherapy. The management of febrile neutropenia is typically algorithm-driven. The aim of this study was to assess the results of a standardized protocol for the treatment of febrile neutropenia. Methods: A retrospective cohort study (2011-2012) was conducted of patients with high-risk neutropenia in a hematology-oncology service. Results: Forty-four episodes of 17 patients with a median age of 48 years (range: 18-78 years) were included. The incidence of febrile neutropenia was 61.4%. The presence of febrile neutropenia was associated with both the duration and severity of neutropenia. Microbiological agents were isolated from different sources in 59.3% of the episodes with bacteremia iso- lated from blood being the most prevalent (81.3%). Multiple drug-resistant gram-negative bacilli were isolated in 62.5% of all microbiologically documented infections. Treatment of 63% of the episodes in which the initial treatment was piperacillin/tazobactam needed to be escalated to meropenem. The mortality rate due to febrile neutropenia episodes was 18.5%. Conclusion: The high rate of gram-negative bacilli resistant to piperacillin/tazobactam (frontline antibiotics in our protocol) and the early need to escalate to carbapenems raises the question as to whether it is necessary to change the current protocol.